Gambaran Sikap Pasien Diabetes Mellitus di Poli Gizi RSUD Dr. R. Goeteng Tarunadibrata Purbalingga terhadap Kunjungan Ulang Konseling Gizi - Wahyuni, Irma; Prihatin, Setyo (Poltekkes Kemenkes Semarang, 2013)
Background: Knowledge of Diabetes Mellitus will be at least more quickly result in complications and this will be a burden to family and community. This lack of community that can impede preventive actions, because it is so related to the economic consequences such as treatment in hospitals and medical facilities or health needs. Counselling is a form of education. Objective: To describe the implementation of nutrition counseling in patients with diabetes mellitus dr. R. Goeteng Tarunadibrata Purbalingga and describe attitudes towards patients with diabetes mellitus re-nutrition counseling. Methods: This descriptive study. The number of samples were patients with diabetes mellitus in Poly Nutrition dr. R. Goeteng Tarunadibrata Purbalingga who meet the criteria of inklusi : patient of diabetes melitus with or without komplikasi, have consultancy mendapt of nutrition in poly nutrition, age woman and man 30 - 80 year, can communicate with goodness and do not illiteracy. While for the criterion of ekslusi: patient of diabetes melitus which do not living in sub-province of Purbalingga. The data obtained included sex, age, education, employment and attitudes of patients obtained by using questionnaires. Results: Attitudes of patients in general have a good attitude toward repeated, this is because of consistency in the attitude not to the same extent in every individual and every object yourself attitude. inconsistent attitude that does not show correspondence between attitude and behavior statements, or easily change from time to time interpretation will be difficult and not much meaningful in understanding and predicting the behavior of the individuals concerned. Conclusion: Consultation nutrition has an important role in helping to control this disease in order to improve the quality of life and prevent various